Manajemen Moving Class Di Sekolah Menengah Pertama Negeri - Amir, Asmah (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2013)
Moving class is a class of learning systems are implemented in SMP move 4 Two Pitue Sidrap. Whenever changing lesson the students will leave the classroom and go to another class in accordance with the subjects that have been scheduled, while the teacher has to wait for a student in the class. Moving class system can increase students' motivation, because the class system moving students will acquire an ever-changing classroom environment so that students can be more eager to accept the lesson. This will indirectly improve student learning outcomes. In order to increase student achievement then manejemen moving class must be considered from the planning, organizing, implementing, and evaluating moving class.